Guidelines for the use of biomarkers Principles, processes and practical consideration - Horváth Andrea Rita; Kis Erika; Dobos Éva (2010)
With the growing availability of new health care technologies and rapidly emerging biomarker discoveries, clinicians need advice on the clinical validity and utility of new tests and whether they improve clinical, patient-centred, organizational or economic outcomes. High quality clinical practice guidelines (CPGs), based on well-designed and conducted test evaluation studies, are tools for translating research into practice and in promoting a value- and evidence-based approach for clinical utilization and reimbursement of new biomarkers. Such study protocols should be appropriate for the questions addressed at each stage of biomarker development: 1/ Basic research into the association of disease with the new biomarker; 2/ Modelling the potential use of the new biomarker in clinical practice; Studies on the 3/ analytic validity; 4/ clinical validity (efficacy); 5/ clinical utility (effectiveness); and 6/ clinical impact (efficiency) of testing. Irrespective of the facts that CPGs potentially influence important clinical decisions and thus patient outcomes, current approaches to CPG development often do not follow the rigorous processes of scientific publications. Guidelines should be outcome oriented; reliable and free from any forms of bias; based on high quality research or on formal consensus when evidence is conflicting or lacking; multidisciplinary; flexible and applicable to various clinical circumstances and patient preferences; clear; cost-effective; appropriately disseminated and implemented; amenable to measurement of their impact in practice; and regularly reviewed and updated. Therefore until guideline-making and reporting standards are improved, all CPGs should be carefully scrutinized for methodological and content validity before being adopted, adapted and used in clinical practice.